A traveler in Siam in the year 1655 : extracts from the journal of Gijsbert Heeck, 16 November 1654 and 12 August-18 October 1655 - Heeck, Gijsbert, 1619-1669.; Terwiel, B. J. (Barend Jan), 1941- (Chiang Mai, Thailand : Silkworm Books, 2008)
Gijsbert Heeck (1619-1669) era un especialista en medicina con la East India Company holandés (VOC). Su diario se basa en las notas diarias que hizo durante su tercer viaje a Oriente. Este volumen lleva las selecciones de su diario que se ocupan de Siam, acompañado por el texto original en holandés.
The manuscript 3 -- The journal and Thai history 4 -- The historical value of the segment concerning Siam 9 -- a. Aftermath of the battle with the Portuguese 9 -- b. Additions to the Thai historical record 11 -- c. Historical geography of the lower Chao Phraya 12 -- d. Gender studies 15 -- e. The lodge, the warehouse, and technology transfer 16 -- f. Ayutthaya in 1655 17 -- g. Reminiscences 17 -- Cultural clashes in Heeck's account 18 -- Technical information on the translation 21 -- A Traveler in Siam in the Year 1655 27 -- Dagelijcxsz Aenteijkeninge 12 Augustus-18 October 1655 76.
Rincón tailandés.
Incluye índice.
Texto en Inglés y holandés.
Keywords: HEECK, GIJSBERT, -- 1619-1669 -- VIAJES -- TAILANDIA; HEECK, GIJSBERT, -- 1619-1669 -- CORRESPONDENCIA, MEMORIAS, ETC; HOLANDESES -- TAILANDIA -- HISTORIA -- SIGLO XVII -- FUENTES; VIAJEROS HOLANDESES -- TAILANDIA -- HISTORIA; TAILANDIA -- DESCRIPCIONES Y VIAJES -- OBRAS ANTERIORES A 1800